2018
DOI: 10.1002/ijc.31815
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity influences drug responsiveness in renal cancer assessed by ex vivo drug testing of multiple patient‐derived cancer cells

Abstract: Renal cell cancer (RCC) has become a prototype example of the extensive intratumor heterogeneity and clonal evolution of human cancers. However, there is little direct evidence on how the genetic heterogeneity impacts on drug response profiles of the cancer cells. Our goal was to determine how genomic clonal evolution impacts drug responses. Finding from our study could help to define the challenge that clonal evolution poses on cancer therapy. We established multiple patient-derived cells (PDCs) from differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
1
23
1
Order By: Relevance
“…We enlarged evaluation of cancer organoids as drug testing model exploring the activity of on-going trial drugs based on multi-kinases inhibition i.e SU11274, Foretinib, Cabozantinib and Levantinib in combination with Everolimus. Normal and tumor organoids isolated from two selected patients were characterized as mutational patterns by Sanger sequencing looking at the most frequent lesions recently associated at therapy in renal cancer 48 (Supplementary Fig. 16–18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We enlarged evaluation of cancer organoids as drug testing model exploring the activity of on-going trial drugs based on multi-kinases inhibition i.e SU11274, Foretinib, Cabozantinib and Levantinib in combination with Everolimus. Normal and tumor organoids isolated from two selected patients were characterized as mutational patterns by Sanger sequencing looking at the most frequent lesions recently associated at therapy in renal cancer 48 (Supplementary Fig. 16–18).…”
Section: Resultsmentioning
confidence: 99%
“…Short Tandem Repeat Analysis for sample Identification in organoid and parental derivative tissues were performed with AmpFℓSTR™ Identifiler™ PCR Amplification Kit (Catalog Number 4322288 Thermofisher Scientific). Mutation scanning of the specific variants selected among frequently published (Saeed K. et al 48 and TCGA genome ATLAS 49 ) was performed by Sanger sequencing using an ABI Prism 3500 Genetic Analyzers (Applied Biosystems) and the ABI BigDye Terminator Sequencing Kit V.3.1 (Applied Biosystems). Primer pairs designed to amplify a specific coding regions of PBMR1, TSC2, VHL, KDM5C, SETD2 and PIK3C2A genes are listed in online Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
“…The PDC cultures that we derived largely retained the characterizing molecular features defining ccRCC evolutionary subtypes during serial passaging and consequently represent attractive tools to study the role of subclones in invasion, metastasis, or therapy resistance. Interestingly, a complementary proof-of-concept study recently indicated the impact of spatial tumor heterogeneity on drug response patterns by establishing PDC cultures from different tumor regions and highlighting their distinct drug response profiles [27]. While truncal driver mutations inherited by all cancer cells could be exploited to find common drug efficacies, PDC models provide the prerequisite to investigate drug response profiles specific to subsets of patients.…”
Section: Discussionmentioning
confidence: 99%
“…e intravascular portion of the renal tumor is not typically biopsied and would be invasive, which is why we focused on the intratumor microbiota profile. Primary renal tumor tissue can be biopsied, but does suffer from genetic heterogeneity and is one of the controversies regarding renal biopsy accuracy for precision medicine and stratification in clinical trials [21][22][23].…”
Section: Discussionmentioning
confidence: 99%